Rekayasa Proses Bisnis Sistem Surveilans Penyakit Tidak Menular berbasis IoT - Irfan Asfy Fakhry Anto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Surveillance is an analytic, systematic, and periodic activity toward diseases or health symptoms so that countermeasures can be done using data processing and dissemination of health epidemiological information to health service providers. Technological developments can be applied to health surveillance activities, e.g., Internet of Things (IoT). This paper aims to find out and analyze business processes, then to conduct process engineering, especially for a non-communicable disease surveillance business processes with an IoT-based technology approach. The methodology used in this paper is business process improvement. This paper produces a design of business process from the stages carried out, including identification, business process analysis, engineering or business process improvement, and business process evaluation, before and after improvement. The business process simulation shows that business process cycle time can be reduced more efficient by an average of 62.9 minutes or 78.77%. It can be concluded that the IoT-based re-engineered business process for the prevention of non-communicable diseases is more efficient in carrying out its activities.